The effect of specific strength training on throwing velocity in overarm throwing: A systematic review - Bao Fredriksen, A.; van den Tillaar, R. (Sports Medicine - Open, 2024)
Background Throwing velocity is an important research topic in sports science, and it is an essential performance variable for athletes in overarm-throwing sports like baseball, team handball, water polo, softball, and cricket. The aim of the present review was to investigate the effect of specific strength training on throwing velocity for overarm throws.